Recycling of the Electronic Waste Applying the Plasma Reactor Technology - Lázár Marián; Jasminská Natália; Čarnogurská Mária; Dobáková Romana (Selected Scientific Papers: Journal of Civil Engineering, 2016)
The following paper discusses a high-temperature gasification process and melting of electronic components and computer equipment using plasma reactor technology. It analyses the marginal conditions of batch processing, as well as the formation of solid products which result from the procedure of waste processing. Attention is also paid to the impact of the emerging products on the environment.